Andrographolide enhances hippocampal BDNF signaling and suppresses neuronal apoptosis, astroglial activation, neuroinflammation, and spatial memory deficits in a rat model of chronic cerebral hypoperfusion - Wang, Da-Peng; Yin, Hang; Lin, Qi; Fang, Shu-Ping; Shen, Jian-Hua; Wu, Yi-Fang; Su, Shao-Hua; Hai, Jian (Naunyn-Schmiedeberg's archives of pharmacology, 2019)
Andrographolide is a medical herbal compound with documented anti-inflammatory activity and therapeutic efficacy in animal models of Alzheimer’s disease, traumatic brain injury, and ischemic stroke. The present study examined the potential therapeutic effects of andrographolide on chronic cerebral hypoperfusion (CCH)–induced hippocampal neuronal damage and cognitive dysfunction. A CCH model was established in male Sprague Dawley (SD) rats using 2-vessel occlusion (2VO). After 4 weeks of CCH, spatial learning and memory were assessed in the Morris water maze and structural damage to the hippocampus by hematoxylin and eosin (HE) staining. Astrocyte activation was examined by immunohistochemical staining and Western blotting for glial fibrillary acid protein (GFAP), while expression levels of the pro-inflammatory cytokine-tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (IL-1β), the apoptosis effector cysteinyl aspartate specific proteinase-3 (caspase-3), and the neuroprotectant brain-derived neurotrophic factor (BDNF) and the TrkB receptor were estimated by Western blotting. After 4 weeks of CCH, the hippocampus of 2VO rats exhibited marked neurodegeneration as well as elevated GFAP, TNF-α, IL-1β, and caspase-3 compared to Sham controls. In addition, spatial learning was impaired compared to Sham controls. Andrographolide treatment during CCH suppressed astrocyte activation as evidenced by reduced GFAP expression, enhanced expression of BDNF and TrkB, improved impaired spatial learning and memory, and reversed upregulated TNF-α, IL-1β, and caspase-3 expression. These results reveal a potential neuroprotective effect of andrographolide on hippocampal neuronal damage and cognitive impairment from CCH due to suppression of astrocyte activation and enhancement of BDNF-TrkB signaling.